Waterproof and anti-fouling ceramic tile joint mixture and preparation method thereof

By blending borosilicate resin and cobalt-based MOF composite modified alkyd resin and superhydrophobic carbon nanotubes @ silica dispersion with other materials, waterproof and stain-resistant ceramic tile joint fillers are prepared, which solves the problem of insufficient water resistance and stain-resistant properties of existing joint fillers, and achieves higher waterproof and stain-resistant properties and service life.

CN119684952AActive Publication Date: 2025-03-25娄城环保(苏州)有限公司

Patent Information

Application Number
CN202510188083.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-25
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

The existing ceramic tile caulks have poor water resistance and stain resistance, which cannot meet the needs of use, shortening their service life.

Method used

Waterproof and stain-resistant ceramic tile joint filler is prepared by blending borosilicate resin and cobalt-based MOF composite modified alkyd resin, superhydrophobic carbon nanotubes @ silica dispersion with cement, lithium mica lithium slag powder, nylon and silicone oil.

Benefits of technology

It significantly enhances the waterproof and stain-resistant properties of the caulking agent, improves the tensile bonding strength, ensures the firmness and stability of the caulking agent, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684952A_ABST
    Figure CN119684952A_ABST
Patent Text Reader

Abstract

The invention discloses a waterproof and anti-fouling ceramic tile joint mixture and a preparation method thereof, and relates to the technical field of building materials. The waterproof and anti-fouling ceramic tile joint mixture is prepared from boron-containing silicon resin and cobalt-based MOF composite modified alkyd resin, super-hydrophobic carbon nano tube and silicon dioxide dispersion, cement, lepidolite lithium slag powder, nylon and silicone oil. The ceramic tile joint mixture is prepared by blending boron-containing silicon resin and cobalt-based MOF composite modified alkyd resin, a super-hydrophobic carbon nano tube and silicon dioxide dispersion, cement, lepidolite lithium slag powder, nylon and silicone oil, the surface of the ceramic tile joint mixture is of a rough structure and has hydrophobicity, and the internal extremely compact structure further reduces permeation of water and dirt. The waterproof and anti-fouling performance is remarkably enhanced, meanwhile, the excellent tensile bonding strength is achieved, the firmness and stability of the joint mixture are ensured, and the service life is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to a waterproof and anti-fouling tile caulking agent and a preparation method thereof. Background Art

[0002] After the tiles are laid, the existence of gaps will destroy the overall beauty. Using caulking agent to fill these gaps can make the decorative surface smoother and smoother, improving the overall aesthetics. At the same time, the caulking agent can also be formulated into a color similar to the building materials as needed to further enhance the decorative effect.

[0003] Sealant is mainly composed of cement, filler, polymer and a small amount of additives. In order to ensure better wear resistance and compressive and flexural strength, the proportion of cement in the seam sealant raw materials is usually higher. However, cement has strong hydrophilicity and poor hydrophobicity, and its surface is easily infiltrated. At the same time, cement will produce defects such as microcracks, various macropores and capillaries during the hydration process. This multi-phase inhomogeneous system composed of pores has a high water absorption rate and is easily infiltrated by aqueous solutions formed by various stains, thus causing pollution.

[0004] The existing technology currently has the following problems:

[0005] Common tile grouts have poor water resistance and stain resistance, cannot meet usage requirements, and also shorten their service life. Summary of the invention

[0006] In view of the above situation, in order to overcome the defects of the prior art, the present invention proposes a waterproof and anti-fouling tile grout, comprising the following components in parts by weight: 10-15 parts of borosilicate resin and cobalt-based MOF composite modified alkyd resin, 15-20 parts of super-hydrophobic carbon nanotube @silica dispersion, 30-40 parts of cement, 20-30 parts of lithium mica lithium slag powder, 2-3 parts of nylon, and 2-3 parts of silicone oil.

[0007] The boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin comprises the following components in parts by weight: 15-20 parts of boron-containing silicone resin, 15-20 parts of cobalt-based MOF, and 60-70 parts of alkyd resin.

[0008] The super-hydrophobic carbon nanotube@silica dispersion comprises the following components in parts by weight: 8-10 parts of carboxyl carbon nanotubes, 10-20 parts of ethyl orthosilicate, and 10-20 parts of gamma-aminopropyltriethoxysilane.

[0009] The preparation method of the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin specifically comprises the following steps:

[0010] (1) 0.8 g of phenyltriethoxysilane, 3.0 g of methyltriethoxysilane and 0.8 g of dimethyldiethoxysilane were added to a 100 mL three-necked round-bottom flask, stirred at 180-200 rpm, heated to 70-80°C, and then slowly dripped 30 mL of a 4% hydrochloric acid solution. After the addition was completed, the mixture was kept at 70-80°C for 1-2 h, and then 50 mL of a mixed solution of boric acid and anhydrous ethanol was dripped into the mixture. The mixture was reacted for 2-3 h, and distilled under reduced pressure to remove water and ethanol small molecular compounds. The silicone resin was discharged. Boron was introduced into the silicone resin, which contained a large number of hydrophobic groups such as methyl and a cross-linked network structure, which blocked the dissolution and penetration of water molecules and reduced the penetration of the aqueous solution formed by dirt, thereby improving the waterproof and anti-fouling properties. The addition of boron can also reduce the shrinkage of cement during the curing process and reduce the risk of cracks, thereby obtaining a boron-containing silicone resin.

[0011] (2) Add cobalt nitrate hexahydrate to 25 mL of N,N-dimethylformamide liquid and stir until completely dissolved. Then add 0.05 g of trimesic acid and stir for 1-2 hours. Transfer the solution to a 50 mL stainless steel reactor with a polytetrafluoroethylene liner. Seal the reactor cover and react at 220-240 ° C for 1-2 hours. Cool down to room temperature. Wash the product with N,N-dimethylformamide liquid and anhydrous ethanol 3-5 times and vacuum dry. The metal organic framework MOF has excellent superhydrophobicity, self-cleaning properties and a dense structure that blocks moisture and dirt. The cobalt-based MOF synthesized with cobalt as the metal source is coated with abundant small particles on the surface, which increases the specific surface area and is conducive to its fusion with the resin. In addition, its dense structure effectively isolates the entry of moisture, thereby improving the waterproof and anti-fouling effect, and obtains a cobalt-based MOF.

[0012] (3) Add the boron-containing silicone resin described in step (1), the cobalt-based MOF described in step (2) and the alkyd resin into a 250 mL four-necked round-bottom flask with a distillation device and a thermometer, then add 10 mL of propylene glycol methyl ether acetate and tetrabutyl titanate liquid respectively, stir evenly, heat to 100-110° C. for dehydration reaction for 0.5-1 h, then heat to 115-125° C. for reaction for 2-3 h, and distill under reduced pressure. The cobalt-based MOF promotes the cross-linking of the boron-containing silicone resin and the alkyd resin, increases the density and complexity of the structure, significantly enhances the water resistance and stain resistance, and improves the tensile bonding strength of the alkyd resin. The alkyd resin is effectively attached to the surface of the substrate, reduces the risk of cracking or falling off, and has excellent durability and stability, thereby obtaining a boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin;

[0013] Preferably, in step (1), the mass fraction of boric acid in the mixed solution of boric acid and anhydrous ethanol is 10-20%. Boric acid greatly improves the strength of the resin through cross-linking, enhances cohesion and adhesion, and can be better adhered to the substrate when used in the caulking agent, enhances tensile bonding strength, and improves firmness and durability.

[0014] Preferably, in step (2), the amount of cobalt nitrate hexahydrate added is 0.06-0.08 g. Cobalt, as a catalyst, can accelerate the cross-linking reaction between resins, form a strong chemical bond, and improve the bonding strength. Cobalt can increase the hardness and flexibility of alkyd resin, prevent it from cracking and falling off. Cobalt can also act as an antioxidant to inhibit the oxidation reaction of the resin and extend the service life.

[0015] The present invention also provides a method for preparing a waterproof and anti-fouling tile caulking agent, which specifically comprises the following steps:

[0016] S1. Dissolve the carboxyl carbon nanotubes in 100 mL of 60-70% ethanol solution, crush the cells and perform ultrasonic dispersion for 1-2 hours, add 6 mL of 6-8% sodium hydroxide solution, stir magnetically for 5-10 minutes, and after sufficient mixing, slowly add 10-20 mL of ethyl orthosilicate, react for 10-12 hours, and then age for 120 hours to obtain silica sol, then add 10-20 mL of γ-aminopropyltriethoxysilane, and continue magnetic stirring for 3-4 hours. Silica is evenly distributed in the network structure of the carboxyl carbon nanotubes, and the carboxymethyl carbon nanotubes are intertwined and stacked to form a flaky rough structure. The composite material is endowed with excellent superhydrophobicity and dispersibility through modification with γ-aminopropyltriethoxysilane, and has extremely low surface energy, thereby significantly improving the water resistance of the material, effectively reducing the contact and entry of water and dirt, and obtaining a superhydrophobic carbon nanotube@silica dispersion;

[0017] S2, cement, lithium mica slag powder, nylon and silicone oil are put into a colloid mill, and the mixture is ground and mixed at a speed of 800-900 rpm for 30-50 min. The lithium mica slag powder is used in cement as a mineral blend, which improves the problems of poor cement adhesion, poor deformation ability and easy cracking. The addition of nylon is conducive to the formation of pores, which provides a skeleton for the rough structure of the super-hydrophobic carbon nanotube @ silicon dioxide dispersion. Silicone oil has lubricating, waterproof and mildew-proof effects. Then, boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin and the super-hydrophobic carbon nanotube @ silicon dioxide dispersion described in step S1 are added, and the grinding and mixing is continued for 1-2 h. Discharging. The boron-silicon resin and cobalt-based MOF-composite modified alkyd resin have excellent bonding strength, can provide high-strength bonding effect between different materials, ensure the firmness of the caulking agent, and the polymer film formed after drying has good waterproof and anti-fouling properties, which can effectively prevent the penetration of water and dirt, and prevent the caulking agent from getting damp and moldy. The super-hydrophobic carbon nanotube@silica dispersion blended with the resin forms a large number of pores and holes, giving a lower surface energy and a rough surface structure, further improving the waterproof and anti-fouling properties, and significantly extending the use effect and durability of the caulking agent, thus obtaining a waterproof and anti-fouling tile caulking agent;

[0018] Preferably, in step S1, the added amount of carboxyl carbon nanotubes is 8.0-10.0 g. The tubular structure of the carboxyl carbon nanotubes further enhances the compactness, which is beneficial to reduce the penetration of moisture and dirt. The carboxyl carbon nanotubes can reduce the adverse effects of structural defects and disorder on mechanical properties, thereby improving the tensile bonding strength.

[0019] The beneficial effects achieved by the present invention are as follows:

[0020] The present invention prepares a tile caulking agent by blending boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin, super-hydrophobic carbon nanotube@silica dispersion with cement, lithium mica lithium slag powder, nylon and silicone oil. The surface presents a rough structure and has hydrophobicity, and the extremely dense structure inside further reduces the penetration of water and dirt, significantly enhances the waterproof and anti-fouling performance, and at the same time, it also has excellent tensile bonding strength, ensures the firm stability of the caulking agent, and effectively prolongs the service life; in the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin, boron element, silicone resin, cobalt element and metal organic framework MOF are introduced into the alkyd resin, which not only increases the density of the structure, effectively reduces the penetration of water and dirt, but also improves the tensile bonding strength of the alkyd resin, so that it can be stably attached to the surface of the substrate, wherein the cobalt-based MOF can also promote the cross-linking reaction of the boron-containing silicone resin and the alkyd resin, further increases the density and complexity of the structure, significantly enhances the waterproof and anti-fouling performance and tensile strength. The invention discloses a kind of waterproof and anti-fouling ceramic tile caulking agent, which is prepared by using boron-silicon resin and cobalt-based MOF composite modified alkyd resin, super-hydrophobic carbon nanotube @ silica dispersion, cement, lithium mica lithium slag powder, nylon and silicone oil, and has excellent tensile bonding strength, reduces the risk of cracking or falling off, and has excellent durability and stability; in the super-hydrophobic carbon nanotube @ silica dispersion, silica is filled and distributed in the network structure of carboxyl carbon nanotubes, reduces the agglomeration of silica particles, and forms a flaky rough structure under the interweaving and stacking of carboxymethyl carbon nanotubes, and through the modification treatment of γ-aminopropyltriethoxysilane, the composite material is endowed with excellent super-hydrophobicity and dispersibility, has extremely low surface energy, and exerts excellent waterproof and anti-fouling properties, wherein the addition of silica particles can improve the bonding effect of the interface, reduce the occurrence of cracking or falling off, and increase the durability of use; the invention uses boron-silicon resin and cobalt-based MOF composite modified alkyd resin, super-hydrophobic carbon nanotube @ silica dispersion, cement, lithium mica lithium slag powder, nylon and silicone oil to prepare a waterproof and anti-fouling ceramic tile caulking agent, which has excellent tensile bonding strength and waterproof and anti-fouling properties, improves the firmness and stability of the caulking agent, and effectively prolongs the service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a scanning electron microscope image of the waterproof and anti-fouling tile caulking agent prepared in Example 1 of the present invention;

[0022] Figure 2 The tensile bonding strength results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0023] Figure 3 The water absorption results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0024] Figure 4 The stain resistance results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0025] Figure 5This is a scanning electron microscope image of the boron-silicon resin and cobalt-based MOF composite modified alkyd resin prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0028] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0029] The sources of the reagents used in the examples are as follows:

[0030] Nylon CAS No: 25038-54-4, brand Yuanye, item number S27531-100g;

[0031] Silicone oil brand: Macklin, item number: V909619-100g;

[0032] Carboxyl carbon nanotubes CAS No: 308068-56-6, brand Aladdin, product number C139822-1g;

[0033] Alkyd resin brand: Kain Chemical, item number: 7344XP 60.

[0034] Example 1

[0035] This embodiment proposes a waterproof and anti-fouling tile caulking agent, comprising the following components in parts by weight: 15 parts of borosilicate resin and cobalt-based MOF composite modified alkyd resin, 15 parts of super-hydrophobic carbon nanotube @silicon dioxide dispersion, 40 parts of cement, 30 parts of lithium mica lithium slag powder, 3 parts of nylon, and 3 parts of silicone oil.

[0036] The boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin comprises the following components in parts by weight: 20 parts of boron-containing silicone resin, 20 parts of cobalt-based MOF and 70 parts of alkyd resin.

[0037] The super-hydrophobic carbon nanotube@silica dispersion comprises the following components in parts by weight: 10 parts of carboxyl carbon nanotubes, 20 parts of ethyl orthosilicate, and 20 parts of gamma-aminopropyltriethoxysilane.

[0038] The preparation method of boron-silicon resin and cobalt-based MOF composite modified alkyd resin specifically comprises the following steps:

[0039] (1) Add 0.8 g of phenyltriethoxysilane, 3.0 g of methyltriethoxysilane, and 0.8 g of dimethyldiethoxysilane into a 100 mL three-necked round-bottom flask, stir at 200 rpm, heat to 80 °C, and slowly drip 30 mL of 4% hydrochloric acid solution. After the addition is complete, keep the temperature at 80 °C for 2 h, and then drip 50 mL of a mixed solution of boric acid and anhydrous ethanol. The mass fraction of boric acid in the mixed solution of boric acid and anhydrous ethanol is 20%. Boric acid greatly improves the strength of the resin through cross-linking. Enhance cohesion and adhesion. Used in caulking agents, it can better adhere to the substrate, enhance tensile bonding strength, improve firmness and durability. React for 3 hours, distill under reduced pressure, remove water and ethanol small molecule compounds, and discharge. Boron is introduced into silicone resin, which contains a large number of hydrophobic groups such as methyl and a cross-linked network structure, blocking the dissolution and penetration of water molecules, and also reducing the penetration of aqueous solutions formed by dirt, improving waterproof and anti-fouling properties. The addition of boron can also reduce the shrinkage of cement during the curing process and reduce the risk of cracks, thus obtaining boron-containing silicone resin.

[0040] (2) Add cobalt nitrate hexahydrate to 25 mL of N,N-dimethylformamide liquid and stir until completely dissolved. The amount of cobalt nitrate hexahydrate added is 0.08 g. Cobalt, as a catalyst, can accelerate the cross-linking reaction between resins, form a strong chemical bond, and improve the bonding strength. Cobalt can also improve the hardness and flexibility of alkyd resins and prevent them from cracking and falling off. Cobalt can also act as an antioxidant to inhibit the oxidation reaction of the resin and extend its service life. Then add 0.05 g of trimesic acid and stir for 2 h. Transfer the solution to 50 mL of polytetrafluoroethylene. The reaction was carried out in a stainless steel reactor with an olefin liner, the lid was tightly sealed, and the reaction was carried out at 240°C for 2 hours, and the reaction was cooled to room temperature. The product was washed with N,N-dimethylformamide liquid and anhydrous ethanol for 5 times, and vacuum dried. The metal organic framework MOF has excellent superhydrophobicity, self-cleaning performance, and a dense structure that blocks moisture and dirt. The cobalt-based MOF synthesized with cobalt as the metal source is wrapped with abundant small particles on the surface, which increases the specific surface area and is conducive to its fusion with the resin. The dense structure effectively isolates the entry of moisture, thereby improving the waterproof and anti-fouling effect, and obtaining the cobalt-based MOF.

[0041] (3) The boron-containing silicone resin described in step (1), the cobalt-based MOF described in step (2) and the alkyd resin are added to a 250 mL four-necked round-bottom flask equipped with a distillation device and a thermometer, and then 10 mL of propylene glycol methyl ether acetate and tetrabutyl titanate liquid are added respectively, stirred evenly, heated to 110° C. for dehydration reaction for 1 hour, and then heated to 125° C. for reaction for 3 hours, and distilled under reduced pressure. The cobalt-based MOF promotes the cross-linking of the boron-containing silicone resin and the alkyd resin, increases the density and complexity of the structure, can significantly enhance the water resistance and stain resistance, and can also improve the tensile bonding strength of the alkyd resin, effectively adhere to the surface of the substrate, reduce the risk of cracking or falling off, and have excellent durability and stability, thereby obtaining a boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin.

[0042] This embodiment provides a method for preparing a waterproof and anti-fouling tile caulking agent, which specifically comprises the following steps:

[0043] S1. Dissolve carboxyl carbon nanotubes in 100 mL of 70% ethanol solution, crush the cells and perform ultrasonic dispersion for 2 h. The amount of carboxyl carbon nanotubes added is 10.0 g. The tubular structure of carboxyl carbon nanotubes further enhances the compactness, which is beneficial to reduce the penetration of water and dirt. In addition, carboxyl carbon nanotubes can reduce the adverse effects of structural defects and disorder on mechanical properties, thereby improving the tensile bonding strength. Add 6 mL of 8% sodium hydroxide solution, stir magnetically for 10 min, mix thoroughly, then slowly add 20 mL of ethyl orthosilicate, and react. After aging for 12 hours, the silica sol was obtained by aging for 120 hours, and then 20 mL of γ-aminopropyltriethoxysilane was added, and the silica was continuously stirred for 4 hours. The silica was evenly distributed in the network structure of the carboxyl carbon nanotubes, and the carboxymethyl carbon nanotubes were intertwined and stacked to form a flaky rough structure. The composite material was modified by γ-aminopropyltriethoxysilane to give it excellent superhydrophobicity and dispersibility, and had extremely low surface energy, thereby significantly improving the water resistance of the material, effectively reducing the contact and entry of water and dirt, and obtaining a superhydrophobic carbon nanotube@silica dispersion;

[0044] S2, cement, lithium mica lithium slag powder, nylon and silicone oil are put into a colloid mill, and the mixture is ground and mixed at a speed of 900 rpm for 50 minutes. The lithium mica lithium slag powder is used in cement as a mineral blend, which improves the problems of poor cement adhesion, poor deformation ability and easy cracking. The addition of nylon is conducive to the formation of pores, which provides a skeleton for the rough structure of the super-hydrophobic carbon nanotube @ silica dispersion. Silicone oil has lubricating, waterproof and mildew-proof effects. Then, boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin and the super-hydrophobic carbon nanotube @ silica dispersion described in step S1 are added, and the grinding and mixing is continued for 2 hours, and the material is discharged. The borosilicate resin and cobalt-based MOF composite modified alkyd resin have excellent bonding strength, can provide high-strength bonding effect between different materials, ensure the firmness of the caulking agent, and the polymer film formed after drying has excellent waterproof and anti-fouling properties, which can effectively prevent the penetration of water and dirt, and avoid the caulking agent from getting damp and moldy. The super-hydrophobic carbon nanotube @silica dispersion is blended with the resin to form a large number of pores and holes, which gives a lower surface energy and a rough surface structure, further improving the waterproof and anti-fouling properties, significantly extending the use effect and durability of the caulking agent, and obtaining a waterproof and anti-fouling tile caulking agent.

[0045] In this embodiment, the prepared waterproof and anti-fouling tile caulking agent was subjected to a scanning electron microscope to observe its microscopic morphology. Figure 1 This is a SEM image of the waterproof and anti-fouling tile caulking agent prepared in Example 1, magnified 50,000 times. Figure 1 The surface of the waterproof and anti-fouling tile caulking agent prepared in this embodiment presents a rough network structure.

[0046] In this example, the prepared boron-containing silicon resin and cobalt-based MOF composite modified alkyd resin were subjected to scanning electron microscopy to observe their microscopic morphology. Figure 5 This is a 400-fold magnified SEM image of the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin prepared in Example 1. Figure 5 The boron-silicon resin and cobalt-based MOF composite modified alkyd resin prepared in this embodiment presents a cross-linked dense structure.

[0047] Example 2

[0048] This embodiment proposes a waterproof and anti-fouling tile caulking agent, comprising the following components in parts by weight: 10 parts of borosilicate resin and cobalt-based MOF composite modified alkyd resin, 20 parts of superhydrophobic carbon nanotube @silicon dioxide dispersion, 30 parts of cement, 20 parts of lithium mica lithium slag powder, 2 parts of nylon, and 2 parts of silicone oil.

[0049] The boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin comprises the following components in parts by weight: 15 parts of boron-containing silicone resin, 15 parts of cobalt-based MOF and 60 parts of alkyd resin.

[0050] The super-hydrophobic carbon nanotube@silica dispersion comprises the following components in parts by weight: 8 parts of carboxyl carbon nanotubes, 10 parts of tetraethyl orthosilicate, and 10 parts of gamma-aminopropyltriethoxysilane.

[0051] The preparation method of boron-silicon resin and cobalt-based MOF composite modified alkyd resin specifically comprises the following steps:

[0052] (1) Add 0.8 g of phenyltriethoxysilane, 3.0 g of methyltriethoxysilane, and 0.8 g of dimethyldiethoxysilane into a 100 mL three-necked round-bottom flask, stir at 180 rpm, heat to 70 °C, and slowly drip 30 mL of 4% hydrochloric acid solution. After the addition is complete, keep the temperature at 70 °C for 1 h, and then drip 50 mL of a mixed solution of boric acid and anhydrous ethanol. The mass fraction of boric acid in the mixed solution of boric acid and anhydrous ethanol is 10%. Boric acid greatly improves the strength of the resin through cross-linking. Enhance cohesion and adhesion. Used in caulking agents, it can better adhere to the substrate, enhance tensile bonding strength, improve firmness and durability. React for 2 hours, distill under reduced pressure, remove water and ethanol small molecule compounds, and discharge. Boron is introduced into silicone resin, which contains a large number of hydrophobic groups such as methyl and a cross-linked network structure, blocking the dissolution and penetration of water molecules, and also reducing the penetration of aqueous solutions formed by dirt, improving waterproof and anti-fouling properties. The addition of boron can also reduce the shrinkage of cement during the curing process and reduce the risk of cracks, thus obtaining boron-containing silicone resin;

[0053] (2) Add cobalt nitrate hexahydrate to 25 mL of N,N-dimethylformamide liquid and stir until completely dissolved. The amount of cobalt nitrate hexahydrate added is 0.06 g. Cobalt, as a catalyst, can accelerate the cross-linking reaction between resins, form a strong chemical bond, and improve the bonding strength. Cobalt can also improve the hardness and flexibility of alkyd resins and prevent them from cracking and falling off. Cobalt can also act as an antioxidant to inhibit the oxidation reaction of the resin and extend its service life. Then add 0.05 g of trimesic acid and stir for 1 hour. Transfer the solution to 50 mL of polytetrafluoroethylene. The reaction was carried out in a stainless steel reactor with an olefin liner, the lid was tightly sealed, and the reaction was carried out at 220°C for 1 hour, and the reaction was cooled to room temperature. The product was washed with N,N-dimethylformamide liquid and anhydrous ethanol for 3 times, and vacuum dried. The metal organic framework MOF has excellent superhydrophobicity, self-cleaning performance, and a dense structure that blocks moisture and dirt. The cobalt-based MOF synthesized with cobalt as the metal source is coated with abundant small particles on the surface, which increases the specific surface area and is conducive to its fusion with the resin. The dense structure effectively isolates the entry of moisture, thereby improving the waterproof and anti-fouling effect, and obtaining the cobalt-based MOF.

[0054] (3) The boron-containing silicone resin described in step (1), the cobalt-based MOF described in step (2) and the alkyd resin are added to a 250 mL four-necked round-bottom flask equipped with a distillation device and a thermometer, and then 10 mL of propylene glycol methyl ether acetate and tetrabutyl titanate liquid are added respectively, stirred evenly, heated to 100° C. for dehydration reaction for 0.5 h, then heated to 115° C. for reaction for 2 h, and distilled under reduced pressure. The cobalt-based MOF promotes the cross-linking of the boron-containing silicone resin and the alkyd resin, increases the density and complexity of the structure, can significantly enhance the water resistance and stain resistance, and can also improve the tensile bonding strength of the alkyd resin, effectively adhere to the surface of the substrate, reduce the risk of cracking or falling off, and have excellent durability and stability, thereby obtaining a boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin.

[0055] This embodiment provides a method for preparing a waterproof and anti-fouling tile caulking agent, which specifically comprises the following steps:

[0056] S1. Dissolve carboxyl carbon nanotubes in 100 mL of 60% ethanol solution, crush the cells and perform ultrasonic dispersion for 1 h. The amount of carboxyl carbon nanotubes added is 8.0 g. The tubular structure of carboxyl carbon nanotubes further enhances the compactness, which is beneficial to reduce the penetration of water and dirt. In addition, carboxyl carbon nanotubes can reduce the adverse effects of structural defects and disorder on mechanical properties, thereby improving the tensile bonding strength. Add 6 mL of 6% sodium hydroxide solution, stir magnetically for 5 min, mix thoroughly, and then slowly add 10 mL of ethyl orthosilicate to react. 10h, and then aged for 120h to obtain silica sol, then 10mL of γ-aminopropyltriethoxysilane was added, and magnetic stirring was continued for 3h, and silicon dioxide was evenly distributed in the network structure of carboxyl carbon nanotubes, and carboxymethyl carbon nanotubes were intertwined and stacked to form a flaky rough structure. The modified treatment of γ-aminopropyltriethoxysilane gave the composite material excellent superhydrophobicity and dispersibility, and had extremely low surface energy, thereby significantly improving the water resistance of the material, effectively reducing the contact and entry of water and dirt, and obtaining a superhydrophobic carbon nanotube@silica dispersion;

[0057] S2, cement, lithium mica lithium slag powder, nylon and silicone oil are put into a colloid mill, and the mixture is ground and mixed at a speed of 800 rpm for 30 minutes. The lithium mica lithium slag powder is used in cement as a mineral blend, which improves the problems of poor cement adhesion, poor deformation ability and easy cracking. The addition of nylon is conducive to the formation of pores, which provides a skeleton for the rough structure of the super-hydrophobic carbon nanotube @ silica dispersion. Silicone oil has lubricating, waterproof and mildew-proof effects. Then, boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin and the super-hydrophobic carbon nanotube @ silica dispersion described in step S1 are added, and the grinding and mixing is continued for 1 hour, and the material is discharged. The borosilicate resin and cobalt-based MOF composite modified alkyd resin have excellent bonding strength, can provide high-strength bonding effect between different materials, ensure the firmness of the caulking agent, and the polymer film formed after drying has excellent waterproof and anti-fouling properties, which can effectively prevent the penetration of water and dirt, and avoid the caulking agent from getting damp and moldy. The super-hydrophobic carbon nanotube @silica dispersion is blended with the resin to form a large number of pores and holes, which gives a lower surface energy and a rough surface structure, further improving the waterproof and anti-fouling properties, significantly extending the use effect and durability of the caulking agent, and obtaining a waterproof and anti-fouling tile caulking agent.

[0058] Example 3

[0059] This embodiment proposes a waterproof and anti-fouling tile caulking agent, comprising the following components in parts by weight: 12.5 parts of borosilicate resin and cobalt-based MOF composite modified alkyd resin, 17.5 parts of superhydrophobic carbon nanotube @silica dispersion, 35 parts of cement, 25 parts of lithium mica lithium slag powder, 2.5 parts of nylon, and 2.5 parts of silicone oil.

[0060] The boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin comprises the following components in parts by weight: 17.5 parts of boron-containing silicone resin, 17.5 parts of cobalt-based MOF and 65 parts of alkyd resin.

[0061] The super-hydrophobic carbon nanotube@silica dispersion comprises the following components in parts by weight: 9 parts of carboxyl carbon nanotubes, 15 parts of tetraethyl orthosilicate, and 15 parts of gamma-aminopropyltriethoxysilane.

[0062] The preparation method of boron-silicon resin and cobalt-based MOF composite modified alkyd resin specifically comprises the following steps:

[0063] (1) 0.8 g of phenyltriethoxysilane, 3.0 g of methyltriethoxysilane and 0.8 g of dimethyldiethoxysilane were added to a 100 mL three-necked round-bottom flask, stirred at a speed of 190 pm, heated to 75 °C and then slowly dripped with 30 mL of a 4% hydrochloric acid solution. After the addition was completed, the mixture was kept at 75 °C for 1.5 h, and then 50 mL of a mixed solution of boric acid and anhydrous ethanol was dripped into the mixture. The mass fraction of boric acid in the mixed solution of boric acid and anhydrous ethanol was 15%. Boric acid greatly improves the strength of the resin through cross-linking, increasing Strong cohesion and adhesion, used in caulking agents to better adhere to the substrate, enhance tensile bonding strength, improve firmness and durability, react for 2.5 hours, vacuum distill, remove water and ethanol small molecule compounds, discharge, introduce boron element into silicone resin, contain a large number of methyl and other hydrophobic groups and cross-linked network structure, block the dissolution and penetration of water molecules, and also reduce the penetration of aqueous solution formed by dirt, improve waterproof and anti-fouling properties, the addition of boron element can also reduce the shrinkage of cement during the curing process, reduce the risk of cracks, and obtain boron-containing silicone resin;

[0064] (2) Add cobalt nitrate hexahydrate to 25 mL of N,N-dimethylformamide liquid and stir until completely dissolved. The amount of cobalt nitrate hexahydrate added is 0.07 g. Cobalt, as a catalyst, can accelerate the cross-linking reaction between resins, form a strong chemical bond, and improve the bonding strength. Cobalt can also improve the hardness and flexibility of alkyd resins and prevent them from cracking and falling off. Cobalt can also act as an antioxidant to inhibit the oxidation reaction of the resin and extend its service life. Then add 0.05 g of trimesic acid and stir for 1.5 h. Transfer the solution to 50 mL of polytetrafluoroethylene. The reaction was carried out in a stainless steel reactor with an ethylene liner, the lid was tightly sealed, and the reaction was carried out at 230°C for 1.5 hours, and the reaction was cooled to room temperature. The product was washed with N,N-dimethylformamide liquid and anhydrous ethanol for 4 times, and vacuum dried. The metal organic framework MOF has excellent superhydrophobicity, self-cleaning performance, and a dense structure that blocks moisture and dirt. The cobalt-based MOF synthesized with cobalt as the metal source is wrapped with abundant small particles on the surface, which increases the specific surface area and is conducive to its fusion with the resin. The dense structure effectively isolates the entry of moisture, thereby improving the waterproof and anti-fouling effect, and obtaining the cobalt-based MOF.

[0065] (3) The boron-containing silicone resin described in step (1), the cobalt-based MOF described in step (2) and the alkyd resin are added to a 250 mL four-necked round-bottom flask equipped with a distillation device and a thermometer, and then 10 mL of propylene glycol methyl ether acetate and tetrabutyl titanate liquid are added respectively, stirred evenly, heated to 105° C. for dehydration reaction for 0.75 h, then heated to 120° C. for reaction for 2.5 h, and distilled under reduced pressure. The cobalt-based MOF promotes the cross-linking of the boron-containing silicone resin and the alkyd resin, increases the density and complexity of the structure, can significantly enhance the water resistance and stain resistance, and can also improve the tensile bonding strength of the alkyd resin, effectively adhere to the surface of the substrate, reduce the risk of cracking or falling off, and have excellent durability and stability, thereby obtaining a boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin.

[0066] This embodiment provides a method for preparing a waterproof and anti-fouling tile caulking agent, which specifically comprises the following steps:

[0067] S1. Dissolve carboxyl carbon nanotubes in 100 mL of 65% ethanol solution, crush the cells and perform ultrasonic dispersion for 1.5 h. The amount of carboxyl carbon nanotubes added is 9.0 g. The tubular structure of carboxyl carbon nanotubes further enhances the compactness, which is beneficial to reduce the penetration of water and dirt. In addition, carboxyl carbon nanotubes can reduce the adverse effects of structural defects and disorder on mechanical properties, thereby improving the tensile bonding strength. Add 6 mL of 7% sodium hydroxide solution, stir magnetically for 7.5 min, mix thoroughly, then slowly add 15 mL of ethyl orthosilicate, and react. After aging for 11 hours, the silica sol was obtained by aging for 120 hours, and then 15 mL of γ-aminopropyltriethoxysilane was added, and the silica was continuously stirred for 3.5 hours. The silica was evenly distributed in the network structure of the carboxyl carbon nanotubes, and the carboxymethyl carbon nanotubes were intertwined and stacked to form a flaky rough structure. The composite material was modified by γ-aminopropyltriethoxysilane to give it excellent superhydrophobicity and dispersibility, and had extremely low surface energy, thereby significantly improving the water resistance of the material, effectively reducing the contact and entry of water and dirt, and obtaining a superhydrophobic carbon nanotube@silica dispersion;

[0068] S2, cement, lithium mica lithium slag powder, nylon and silicone oil are put into a colloid mill, and the mixture is ground and mixed at a speed of 850rpm for 40min. The lithium mica lithium slag powder is used in cement as a mineral blend, which improves the problems of poor cement adhesion, poor deformation ability and easy cracking. The addition of nylon is conducive to the formation of pores, which provides a skeleton for the rough structure of the super-hydrophobic carbon nanotube @ silicon dioxide dispersion. Silicone oil has lubricating, waterproof and mildew-proof effects. Then, boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin and the super-hydrophobic carbon nanotube @ silicon dioxide dispersion described in step S1 are added, and the grinding and mixing is continued for 1.5h. The material, the borosilicate resin and the cobalt-based MOF composite modified alkyd resin have excellent bonding strength, can provide a high-strength bonding effect between different materials, ensure the firmness of the caulking agent, and the polymer film formed after drying has good waterproof and anti-fouling properties, which can effectively prevent the penetration of water and dirt, and avoid the caulking agent from getting damp and moldy. The super-hydrophobic carbon nanotube @silica dispersion is blended with the resin to form a large number of pores and holes, which gives a lower surface energy and a rough surface structure, further improving the waterproof and anti-fouling properties, significantly extending the use effect and durability of the caulking agent, and obtaining a waterproof and anti-fouling tile caulking agent.

[0069] Example 4

[0070] This embodiment proposes a waterproof and anti-fouling tile caulking agent, comprising the following components in parts by weight: 15 parts of borosilicate resin and cobalt-based MOF composite modified alkyd resin, 20 parts of super-hydrophobic carbon nanotube @silicon dioxide dispersion, 40 parts of cement, 20 parts of lithium mica lithium slag powder, 2 parts of nylon, and 2 parts of silicone oil.

[0071] The boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin comprises the following components in parts by weight: 20 parts of boron-containing silicone resin, 20 parts of cobalt-based MOF and 70 parts of alkyd resin.

[0072] The super-hydrophobic carbon nanotube@silica dispersion comprises the following components in parts by weight: 10 parts of carboxyl carbon nanotubes, 20 parts of ethyl orthosilicate, and 20 parts of gamma-aminopropyltriethoxysilane.

[0073] The preparation method of boron-silicon resin and cobalt-based MOF composite modified alkyd resin specifically comprises the following steps:

[0074] (1) Add 0.8 g of phenyltriethoxysilane, 3.0 g of methyltriethoxysilane, and 0.8 g of dimethyldiethoxysilane into a 100 mL three-necked round-bottom flask, stir at 200 rpm, heat to 80 °C, and slowly drip 30 mL of 4% hydrochloric acid solution. After the addition is complete, keep the temperature at 80 °C for 1 h, and then drip 50 mL of a mixed solution of boric acid and anhydrous ethanol. The mass fraction of boric acid in the mixed solution of boric acid and anhydrous ethanol is 20%. Boric acid greatly improves the strength of the resin through cross-linking. Enhance cohesion and adhesion. Used in caulking agents, it can better adhere to the substrate, enhance tensile bonding strength, improve firmness and durability. React for 2 hours, distill under reduced pressure, remove water and ethanol small molecule compounds, and discharge. Boron is introduced into silicone resin, which contains a large number of hydrophobic groups such as methyl and a cross-linked network structure, blocking the dissolution and penetration of water molecules, and also reducing the penetration of aqueous solutions formed by dirt, improving waterproof and anti-fouling properties. The addition of boron can also reduce the shrinkage of cement during the curing process and reduce the risk of cracks, thus obtaining boron-containing silicone resin;

[0075] (2) Add cobalt nitrate hexahydrate to 25 mL of N,N-dimethylformamide liquid and stir until completely dissolved. The amount of cobalt nitrate hexahydrate added is 0.08 g. Cobalt, as a catalyst, can accelerate the cross-linking reaction between resins, form a strong chemical bond, and improve the bonding strength. Cobalt can also improve the hardness and flexibility of alkyd resins and prevent them from cracking and falling off. Cobalt can also act as an antioxidant to inhibit the oxidation reaction of the resin and extend its service life. Then add 0.05 g of trimesic acid and stir for 1 hour. Transfer the solution to 50 mL of polytetrafluoroethylene. The reaction was carried out in a stainless steel reactor with an olefin liner, the reactor cover was sealed and the reaction was carried out at 240°C for 1 hour, and the reaction was cooled to room temperature. The product was washed with N,N-dimethylformamide liquid and anhydrous ethanol for 5 times, and vacuum dried. The metal organic framework MOF has excellent superhydrophobicity, self-cleaning performance and a dense structure that blocks moisture and dirt. The cobalt-based MOF synthesized with cobalt as the metal source is wrapped with abundant small particles on the surface, which increases the specific surface area and is conducive to its fusion with the resin. The dense structure effectively isolates the entry of moisture, thereby improving the waterproof and anti-fouling effect, and obtaining the cobalt-based MOF.

[0076] (3) The boron-containing silicone resin described in step (1), the cobalt-based MOF described in step (2) and the alkyd resin are added to a 250 mL four-necked round-bottom flask equipped with a distillation device and a thermometer, and then 10 mL of propylene glycol methyl ether acetate and tetrabutyl titanate liquid are added respectively, stirred evenly, heated to 110° C. for dehydration reaction for 0.5 h, then heated to 125° C. for reaction for 2 h, and distilled under reduced pressure. The cobalt-based MOF promotes the cross-linking of the boron-containing silicone resin and the alkyd resin, increases the density and complexity of the structure, can significantly enhance the water resistance and stain resistance, and can also improve the tensile bonding strength of the alkyd resin, effectively adhere to the surface of the substrate, reduce the risk of cracking or falling off, and have excellent durability and stability, thereby obtaining a boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin.

[0077] This embodiment provides a method for preparing a waterproof and anti-fouling tile caulking agent, which specifically comprises the following steps:

[0078] S1. Dissolve carboxyl carbon nanotubes in 100 mL of 70% ethanol solution, crush the cells and perform ultrasonic dispersion for 1 h. The amount of carboxyl carbon nanotubes added is 10.0 g. The tubular structure of carboxyl carbon nanotubes further enhances the compactness, which is beneficial to reduce the penetration of water and dirt. In addition, carboxyl carbon nanotubes can reduce the adverse effects of structural defects and disorder on mechanical properties, thereby improving the tensile bonding strength. Add 6 mL of 8% sodium hydroxide solution, stir magnetically for 5 min, mix thoroughly, and then slowly add 20 mL of ethyl orthosilicate to react. 10h, and then aged for 120h to obtain silica sol, then 20mL of γ-aminopropyltriethoxysilane was added, and magnetic stirring was continued for 3h, and silicon dioxide was evenly distributed in the network structure of carboxyl carbon nanotubes, and carboxymethyl carbon nanotubes were intertwined and stacked to form a flaky rough structure. The composite material was modified by γ-aminopropyltriethoxysilane to give it excellent superhydrophobicity and dispersibility, and had extremely low surface energy, thereby significantly improving the water resistance of the material, effectively reducing the contact and entry of water and dirt, and obtaining a superhydrophobic carbon nanotube@silica dispersion;

[0079] S2, cement, lithium mica lithium slag powder, nylon and silicone oil are put into a colloid mill, and the mixture is ground and mixed at a speed of 900 rpm for 30 minutes. The lithium mica lithium slag powder is used in cement as a mineral blend, which improves the problems of poor cement adhesion, poor deformation ability and easy cracking. The addition of nylon is conducive to the formation of pores, which provides a skeleton for the rough structure of the super-hydrophobic carbon nanotube @ silica dispersion. Silicone oil has lubricating, waterproof and mildew-proof effects. Then, boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin and the super-hydrophobic carbon nanotube @ silica dispersion described in step S1 are added, and the grinding and mixing is continued for 1 hour, and the material is discharged. The borosilicate resin and cobalt-based MOF composite modified alkyd resin have excellent bonding strength, can provide high-strength bonding effect between different materials, ensure the firmness of the caulking agent, and the polymer film formed after drying has excellent waterproof and anti-fouling properties, which can effectively prevent the penetration of water and dirt, and avoid the caulking agent from getting damp and moldy. The super-hydrophobic carbon nanotube @silica dispersion is blended with the resin to form a large number of pores and holes, which gives a lower surface energy and a rough surface structure, further improving the waterproof and anti-fouling properties, significantly extending the use effect and durability of the caulking agent, and obtaining a waterproof and anti-fouling tile caulking agent.

[0080] Comparative Example 1

[0081] This comparative example provides a waterproof and anti-fouling ceramic tile grout, which is different from Example 1 in that the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin does not contain boron-containing silicone resin; the preparation method of the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin does not include step (1); the preparation method of the waterproof and anti-fouling ceramic tile grout is the same as that of Example 1.

[0082] Comparative Example 2

[0083] This comparative example provides a waterproof and anti-fouling ceramic tile grout, which is different from Example 1 in that the boron-silicon resin and cobalt-based MOF composite modified alkyd resin does not contain cobalt-based MOF; the preparation method of the boron-silicon resin and cobalt-based MOF composite modified alkyd resin does not include step (2); the preparation method of the waterproof and anti-fouling ceramic tile grout is the same as that of Example 1.

[0084] Comparative Example 3

[0085] This comparative example provides a waterproof and anti-fouling tile grout, which differs from Example 1 in that the superhydrophobic carbon nanotube@silica dispersion does not contain carboxyl carbon nanotubes and γ-aminopropyltriethoxysilane; the preparation method of the boron silicon resin and the cobalt-based MOF composite modified alkyd resin is the same as that of Example 1; and carboxyl carbon nanotubes and γ-aminopropyltriethoxysilane are not added in step S1 of the preparation method of the waterproof and anti-fouling tile grout.

[0086] Experimental Example 1

[0087] Firmness and stability test

[0088] Test sample: the waterproof and anti-fouling tile grout prepared in Examples 1-4 and Comparative Examples 1-3.

[0089] Test method: The test sample is made into a specimen with a size of 40mm×40mm×160mm, and the shaped specimen is cured with plastic film. After 7 days, the mold is removed and then covered with polyethylene film for another 7 days. The specimen for tensile adhesion test is cured according to (JG158-2004). The test steps are as follows: Use AB glue to glue a 40mm×40mm×15mm iron head on the specimen, and control the pulling speed of the iron head to measure the tensile adhesion strength (MPa) of the sample at a speed of 5 mm per minute.

[0090] Figure 2 The tensile bonding strength result diagram of Examples 1-4 and Comparative Examples 1-3 is shown in the figure; as shown in the figure, the tensile bonding strength of Examples 1-4 is 1.46-1.65MPa, indicating that the tensile bonding strength is strong, which is conducive to firm stability; the tensile bonding strength of Comparative Examples 1-3 is 0.72-0.98MPa, indicating that the tensile bonding strength is weak, which is not conducive to firm stability; the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin of Comparative Example 1 does not contain boron-containing silicone resin, and the silicon-oxygen bonds in the silicone resin and the boron-oxygen bonds formed by the introduction of boron elements cannot play an improving role in the tensile bonding performance of the material. This results in weak tensile bonding strength, which is not conducive to firm stability; the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin in Comparative Example 2 does not contain cobalt-based MOF, which is not conducive to promoting the cross-linking reaction between the boron-containing silicone resin and the alkyd resin, resulting in weak tensile bonding strength, which is not conducive to firm stability; the super-hydrophobic carbon nanotube@silica dispersion in Comparative Example 3 does not contain carboxyl carbon nanotubes and γ-aminopropyltriethoxysilane, which increases the adverse effects of structural defects and disorder on mechanical properties, and is not conducive to the dispersion uniformity of silica particles, resulting in weak tensile bonding strength, which is not conducive to firm stability.

[0091] Experimental Example 2

[0092] Waterproof test

[0093] Test sample: the waterproof and anti-fouling tile grout prepared in Examples 1-4 and Comparative Examples 1-3.

[0094] Test method: Referring to the method in DL / T5126-2001 "Test Procedure for Polymer Cement Mortar", the test sample was prepared into a specimen with a size of 40mm×40mm×10mm, cured for 28 days, and the water absorption (%) was measured.

[0095] Figure 3The water absorption results of Examples 1-4 and Comparative Examples 1-3 are shown in the figure; as shown in the figure, the water absorption of Examples 1-4 is 0.3-1.5%, indicating good water resistance; the water absorption of Comparative Examples 1-3 is 8.7-14.5%, indicating poor water resistance; the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin of Comparative Example 1 does not contain boron-containing silicone resin, lacks hydrophobic groups and cross-linked network structures, is not conducive to blocking the dissolution and penetration of water molecules, resulting in poor water resistance; the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin of Comparative Example 2 The alkyd resin does not contain cobalt-based MOF, which can neither provide MOF with excellent hydrophobic properties nor further promote the cross-linking reaction between the boron silicone resin and the alkyd resin, which is not conducive to the compactness and complexity of the structure, resulting in poor waterproofness; the super-hydrophobic carbon nanotube@silica dispersion of Comparative Example 3 does not contain carboxyl carbon nanotubes and γ-aminopropyltriethoxysilane, and cannot exert the barrier effect of the tubular structure on moisture, nor can it be modified with γ-aminopropyltriethoxysilane to impart super-hydrophobicity and dispersibility, resulting in poor waterproofness.

[0096] Experimental Example 3

[0097] Antifouling test

[0098] Test sample: the waterproof and anti-fouling tile grout prepared in Examples 1-4 and Comparative Examples 1-3.

[0099] Test method: Referring to the specimen preparation method of JG / T298-2010 "Architectural Interior Putty", the test sample is molded onto a 155mm×85mm tinplate with a thickness of 3mm. It is cured for 28 days under standard test conditions. Three drops of 1:1 diluted soy sauce are added to the surface of the specimen, and it is retained for 30 minutes. It is then wiped and cleaned, and the stain resistance level is visually inspected. The stain resistance level is divided into five levels:

[0100] Level 1 means it can be cleaned by gently wiping with a hot water sponge;

[0101] Level 2 means it can be cleaned by gently wiping with a mild detergent and a sponge;

[0102] Level 3 means it can be cleaned by wiping vigorously with a general detergent and a sponge;

[0103] Level 4 means it can be cleaned with a solvent-based or acidic cleaner and vigorous wiping with a sponge;

[0104] Level 5 means that it cannot be cleaned using any of the above methods.

[0105] Figure 4The stain resistance result diagram of Examples 1-4 and Comparative Examples 1-3 is shown in the figure; as shown in the figure, the stain resistance grade of Examples 1-4 is 1-2, indicating that the stain resistance is better; the stain resistance grade of Comparative Examples 1-3 is 3-4, indicating that the stain resistance is poor; the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin of Comparative Example 1 does not contain boron-containing silicone resin, which is not conducive to increasing the density of the structure, increases the penetration of the aqueous solution formed by the dirt, and leads to poor stain resistance; the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin of Comparative Example 2 does not contain cobalt-based MOF, which can neither provide a barrier to moisture and dirt. The MOF that allows dirt to enter cannot further promote the cross-linking reaction of boron silicone resin and alkyd resin, which is not conducive to the compactness and complexity of the structure, and is not conducive to blocking the penetration of dirt, resulting in poor anti-fouling performance; the super-hydrophobic carbon nanotube @ silica dispersion of comparative example 3 does not contain carboxyl carbon nanotubes and γ-aminopropyltriethoxysilane, and cannot exert the barrier effect of the tubular structure on dirt, nor can it be modified by γ-aminopropyltriethoxysilane, which is not conducive to dispersion compatibility, limits the role of the super-hydrophobic carbon nanotube @ silica dispersion, and results in poor anti-fouling performance.

[0106] The above experimental results show that the firm stability, water resistance and antifouling properties of Examples 1-4 of the present invention are significantly better than those of Comparative Examples 1-3. Among them, Example 1 using boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin and super-hydrophobic carbon nanotubes @ silica dispersion has stronger tensile bonding strength, better water resistance and better antifouling properties. The boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin introduce boron, silicone resin, cobalt and metal organic framework MOF, which not only increases the density of the structure, effectively reduces the penetration of water and dirt, but also improves the tensile bonding strength of the alkyd resin. Among them, the cobalt-based MOF also It can promote the cross-linking reaction of boron silicone resin and alkyd resin, further increase the density and complexity of the structure, significantly enhance the waterproof and anti-fouling properties and tensile bonding strength, and reduce the risk of cracking or falling off. In the superhydrophobic carbon nanotube @silica dispersion, silica is filled and distributed in the network structure of carboxyl carbon nanotubes, which reduces the agglomeration of silica particles. Moreover, under the interweaving and stacking of carboxymethyl carbon nanotubes, a flaky rough structure is formed. Through the modification treatment of γ-aminopropyltriethoxysilane, the composite material is endowed with excellent superhydrophobicity and dispersibility, has extremely low surface energy, and exhibits excellent waterproof and anti-fouling properties.

[0107] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0108] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A waterproof and anti-fouling tile caulking agent, characterized in that: The waterproof and anti-fouling tile caulking agent comprises the following components in parts by weight: 10-15 parts of boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin, 15-20 parts of super-hydrophobic carbon nanotube@silica dispersion, 30-40 parts of cement, 20-30 parts of lithium mica lithium slag powder, 2-3 parts of nylon, and 2-3 parts of silicone oil; the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin comprises the following components in parts by weight: 15-20 parts of boron-containing silicone resin, 15-20 parts of cobalt-based MOF, and 60-70 parts of alkyd resin; the super-hydrophobic carbon nanotube@silica dispersion comprises the following components in parts by weight: 8-10 parts of carboxyl carbon nanotubes, 10-20 parts of tetraethyl orthosilicate, and 10-20 parts of γ-aminopropyltriethoxysilane.

2. A method for preparing the waterproof and anti-fouling tile caulking agent according to claim 1, characterized in that: The specific steps include: S1. Dissolve the carboxyl carbon nanotubes in 100 mL of 60-70% ethanol solution, crush the cells and perform ultrasonic dispersion for 1-2 h, add 6 mL of 6-8% sodium hydroxide solution, stir magnetically for 5-10 min, mix thoroughly, slowly add 10-20 mL of ethyl orthosilicate, react for 10-12 h, and age for 120 h to obtain silica sol, then add 10-20 mL of γ-aminopropyltriethoxysilane, continue magnetic stirring for 3-4 h, and obtain superhydrophobic carbon nanotube@silica dispersion; S2. Put cement, lithium mica lithium slag powder, nylon and silicone oil into a colloid mill, grind and mix at a speed of 800-900 rpm for 30-50 minutes, then add boron silicone resin and cobalt-based MOF composite modified alkyd resin, and the super hydrophobic carbon nanotube @silica dispersion described in step S1, continue grinding and mixing for 1-2 hours, and discharge the material to obtain a waterproof and anti-fouling tile caulking agent.

3. The method for preparing the waterproof and anti-fouling tile caulking agent according to claim 2, characterized in that: In step S1, the amount of carboxyl carbon nanotubes added is 8.0-10.0 g.

4. The method for preparing the waterproof and anti-fouling tile caulking agent according to claim 3, characterized in that: The preparation method of the boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin specifically comprises the following steps: (1) 0.8 g of phenyltriethoxysilane, 3.0 g of methyltriethoxysilane and 0.8 g of dimethyldiethoxysilane were added to a 100 mL three-necked round-bottom flask, stirred at 180-200 rpm, heated to 70-80°C, and then slowly dripped with 30 mL of a 4% hydrochloric acid solution. After the addition was completed, the mixture was kept at 70-80°C for 1-2 h, and then 50 mL of a mixed solution of boric acid and anhydrous ethanol was dripped into the mixture, and the mixture was reacted for 2-3 h. The mixture was distilled under reduced pressure to remove water and ethanol small molecular compounds, and the material was discharged to obtain a boron-containing silicone resin; (2) Add cobalt nitrate hexahydrate to 25 mL of N,N-dimethylformamide liquid and stir until completely dissolved. Then add 0.05 g of trimesic acid and stir for 1-2 h. Transfer the solution to a 50 mL stainless steel reactor with a polytetrafluoroethylene liner. Seal the reactor lid and react at 220-240 °C for 1-2 h. Cool to room temperature. Wash the product with N,N-dimethylformamide liquid and anhydrous ethanol for 3-5 times and vacuum dry to obtain a cobalt-based MOF. (3) The boron-containing silicone resin described in step (1), the cobalt-based MOF described in step (2) and the alkyd resin are added to a 250 mL four-necked round-bottom flask equipped with a distillation device and a thermometer, and then 10 mL of propylene glycol methyl ether acetate and tetrabutyl titanate liquid are added respectively, stirred evenly, heated to 100-110° C. for dehydration reaction for 0.5-1 h, then heated to 115-125° C. for reaction for 2-3 h, and distilled under reduced pressure to obtain a boron-containing silicone resin and cobalt-based MOF composite modified alkyd resin.

5. The method for preparing the waterproof and anti-fouling tile caulking agent according to claim 4, characterized in that: In step (1), in the mixed solution of boric acid and anhydrous ethanol, the mass fraction of boric acid is 10-20%.

6. The method for preparing the waterproof and anti-fouling tile caulking agent according to claim 5, characterized in that: In step (2), the amount of cobalt nitrate hexahydrate added is 0.06-0.08 g.

Citation Information

Patent Citations

  • Ceramic tile joint mixture and preparation method thereof

    CN107337403A

  • Porous carbon coated nano metal cobalt composite catalyst as well as preparation and application thereof

    CN108435177A

  • Preparation method of modified waterborne alkyd resin, soybean-based adhesive, and application of soybean-based adhesive in bamboo and wood shaving boards

    CN111171299A

  • Colored pasty joint mixture for pervious concrete and preparation process of colored pasty joint mixture

    CN113512392A

  • Anti-falling single-component ceramic tile back adhesive and preparation method thereof

    CN118185512A

Cited By

  • Joint mixture for aviation aircraft metal component and preparation method of joint mixture

    CN120574557A

  • Pipeline anti-corrosion material and construction process

    CN120623909A